A novel transcriptome-derived SNPs array for tench (Tinca tinca L.) - Kumar, Girish; Langa, Jorge; Montes, Iratxe; Conklin, Darrell; Kocour, Martin; Kohlmann, Klaus; Estonba, Andone (PloS one, 2019)
Tench (Tinca tinca L.) has great economic potential due to its high rate of fecundity and long-life span. Population genetic studies based on allozymes, microsatellites, PCR-RFLP and sequence analysis of genes and DNA fragments have revealed the presence of Eastern and Western phylogroups. However, the lack of genomic resources for this species has complicated the development of genetic markers. In this study, the tench transcriptome and genome were sequenced by high-throughput sequencing. A total of 60,414 putative SNPs were identified in the tench transcriptome using a computational pipeline. A set of 96 SNPs was selected for validation and a total of 92 SNPs was validated, resulting in the highest conversion and validation rate for a non-model species obtained to date (95.83%). The validated SNPs were used to genotype 140 individuals belonging to two tench breeds (Tabor and Hungarian), showing low (FST = 0.0450) but significant (<0.0001) genetic differentiation between the two tench breeds. This implies that set of validated SNPs array can be used to distinguish the tench breeds and that it might be useful for studying a range of associations between DNA sequence and traits of importance. These genomic resources created for the tench will provide insight into population genetics, conservation fish stock management, and aquaculture.
Keywords: transkriptom; druhová specificita; Male; populační genetika; Breeding; rybářství; Genetics, Population; fylogeneze; Česká republika; Phylogeny; Transcriptome; mužské pohlaví; jednonukleotidový polymorfismus; Species Specificity; chov; Cyprinidae; genetické markery; Czech Republic; genom; Animals; Polymorphism, Single Nucleotide; ženské pohlaví; Fisheries; zvířata; Genome; genová ontologie; Gene Ontology; Female; Genetic Markers